2018
DOI: 10.1021/acs.est.8b00735
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Organic Compounds in Water by Unactivated Peroxymonosulfate

Abstract: Peroxymonosulfate (HSO and PMS) is an optional bulk oxidant in advanced oxidation processes (AOPs) for treating wastewaters. Normally, PMS is activated by the input of energy or reducing agent to generate sulfate or hydroxyl radicals or both. This study shows that PMS without explicit activation undergoes direct reaction with a variety of compounds, including antibiotics, pharmaceuticals, phenolics, and commonly used singlet-oxygen (O) traps and quenchers, specifically furfuryl alcohol (FFA), azide, and histid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
187
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 688 publications
(206 citation statements)
references
References 57 publications
16
187
3
Order By: Relevance
“…Electron paramagnetic resonance (EPR) spectra ( Fig. 2b) showed that by applying the trapping agent 2,2,6,6-tetramethylpiperidine (TEMP), the typical triplet signal (1:1:1, a(N) = 16.9 G) of 2,2,6,6-tetramethyl-4-piperidinol-N-oxyl (TEMPO) in Region C (blue line) was observed, indicating the presence of 1 O 2 in the permeate 8,48 . Detailed EPR measurement is provided in the Supplementary methods; the EPR spectrum of the blank control solution, i.e., 100 mM Na 2 SO 4 with 25 mM TEMP, is provided in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Electron paramagnetic resonance (EPR) spectra ( Fig. 2b) showed that by applying the trapping agent 2,2,6,6-tetramethylpiperidine (TEMP), the typical triplet signal (1:1:1, a(N) = 16.9 G) of 2,2,6,6-tetramethyl-4-piperidinol-N-oxyl (TEMPO) in Region C (blue line) was observed, indicating the presence of 1 O 2 in the permeate 8,48 . Detailed EPR measurement is provided in the Supplementary methods; the EPR spectrum of the blank control solution, i.e., 100 mM Na 2 SO 4 with 25 mM TEMP, is provided in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that 1 O 2 can be produced through PMS selfdecomposition, while its generation is highly dependent on solution pH. Yang et al 29 found that this reaction is mainly occurred under slightly alkaline pH (pH ¼ 9.4), while it is hardly occurred at pH 7.0. The experiment in this study was carried out in a phosphate buffer at pH 7.0, thus 1 O 2 was barely produced in current conditions in this study.…”
Section: Degradation Of Dcf By Uv Pms and Uv/pmsmentioning
confidence: 99%
“…26 Transition metals (e.g., Fe 2+ , Cu 2+ , Mn 2+ and Co 2+ ) are efficient activators for PMS and PDS, but they may cause the risk of secondary pollution. Although PMS can undergo self-decomposition under slightly alkaline condition, singlet oxygen ( 1 O 2 ) is mainly produced, 29 and this process increases the dosage of alkalis. High energy input such as heat and ultraviolet (UV) are other types of common methods which split PMS or PDS into SO 4 c À .…”
Section: Introductionmentioning
confidence: 99%
“…However, only approximately 35.5 ± 3.2% of CAP was degraded in the PMS-alone system. It has been reported that unactivated PMS could directly react with organic compounds via nonradical pathways, but this direct reaction was highly dependent on the solution pH and ionic strength (Yang et al, 2018). The k app value of CAP in the Co 3 O 4 -BC/PMS system was 0.3361 min À1 , which was 5.1, 7.2 and 19.4 times greater than the value in the Co 3 O 4 /PMS (0.0664 min À1 ), PMS-alone (0.0467 min À1 ) and BC/ PMS (0.0173 min À1 ) systems, respectively.…”
Section: Chloramphenicols Degradation In the Co 3 O 4 -Bc/pms Systemmentioning
confidence: 99%